Impulsivity predicts weight loss after obesity surgery - Kulendran,M; Borovoi,L; Purkayastha,S; Darzi,A; Vlaev,I (Surgery for Obesity and Related Diseases, 2017)
ObjectiveThere is evidence that executive function, and specifically inhibitory control, is related to obesity and eating behavior. The goal of this study was to determine whether personality traits and inhibitory control predict weight loss after bariatric procedures. Although the impressive weight reduction after bariatric surgery has been shown in short- and medium-term studies, the effect of personality traits on this reduction is uncertain. Specifically, the effect of impulsivity is still largely unknown.SettingPatients attending either a multidisciplinary information session or outpatient clinic at the Imperial Weight Management Centre were recruited with informed consent into the trial over a 4-month period from January to April 2013. Participants were invited to attend behavioral testing on an outpatient basis in a silent room invigilated by a single researcher.MethodsForty-five bariatric patients participated in the study (25 patients had a gastric bypass, with a mean BMI of 41.8 and age of 39.0 years; 20 had a sleeve gastrectomy, with a mean BMI of 47.2 and age of 49.0 years). All patients completed personality measures of impulsivity—Barratt’s Impulsivity Scale, as well as behavioral measures of impulsivity—the stop-signal reaction-time (SSRT) task measuring inhibitory control and the temporal discounting task measuring reward processing. Those measures were examined in relation to weight loss 6 months after surgery.ResultsThe surgical procedure and changes in the behavioral measure of inhibitory control (SSRT) were found to be significant predictors of reduction in body mass index (BMI) in patients undergoing bariatric surgery. The sleeve gastrectomy group found a reduction in BMI of 14.1%, which was significantly less than the 25% reduction in BMI in the gastric bypass group. The direction (parameter estimate) of the significant effect was positive for SSRT change, which indicates that pre- and postreduction in impulsivity predicts red